How Harm Reduction Programs Work in The Context of Village and Commune Safety Policy: Lessons Learned from A National Non-Governmental Organization in Cambodia - Tuot Sovannary; Heng Sopheab; Chhea Chhorvann; Salonga Eunice; Yi Siyan (Journal of Addiction Disorder and Rehabilitation, 2017)
This paper aims to examine the challenges and implications of the Village and Commune Safety Policy (VCSP) on harm-reduction programs and describe lessons learned from a harm-reduction program within the context of the VCSP in Cambodia. Data were collected from a monitoring and evaluation database and reports of a drop-in center that provides a wide range of harm-reduction services. In addition, qualitative data were collected through key informant interviews and focus group discussions with 38 participants including people who use drugs (PWUD) and people who inject drugs (PWID). Desk reviews and consultative meetings with key stakeholders were also conducted. In total, 496 PWUD were registered into the program between 2010 and 2012, of which 22.4% were PWID, and 15.0% were women. The mean age of participants was 26 years old. HIV prevalence among PWUD was 1.0% compared to 16.2% among PWID. Remarkable achievements were observed such as high uptake of services by PWUD and PWID with active referrals to methadone maintenance treatment (MMT) and voluntary HIV confidential counseling and testing (VCCT). However, distribution of clean needles and syringes in communities was limited. Also, the newly initiated needle and syringe program (NSP) based in pharmacies failed to reach PWUD and PWID. Appropriate coordination and collaboration with law enforcement and authorities were observed given the complexity of the VCSP. However, the implementation of the VCSP poses challenges including NSP and accessibility to harm reduction services. For future successes of harm-reduction programs, it is important to maintain close coordination and collaboration between program implementers and local authorities with mutual understanding and flexibility.
Keywords: People who use drugs (PWUD)